Toleransi Religius, Antara Pluralisme dan Pluralitas Agama dalam Perspektif Al-Quran - Purnomo, Bagus (Lajnah Pentashihan Mushaf Al-Qur'an, 2013)
The emergence of the violence issues concerning religious doctrine is separated from the increasing of the cases of the intolerance in Indonesia. It is for that reason that the discourse about pluralism and plurality of religion becomes the interesting topic. Briefly, the two words above have the same meaning for its similarity in their original form that is Ã¢â‚¬Å“PluralÃ¢â‚¬Â. However, empirically, those two words have the basic difference then it is added by the word religion in the end of the word (suffix). If the plurality of religion is meant to be the variety of religions, then the meaning of pluralism changes to be the uniformity of religion which eventually arising polemic in Indonesia. Plurality of religion is an unavoidable phenomenon from God.(Sunnatullah). This writing tries to explain how the the QurÃ¢â‚¬â„¢an Ã¢â‚¬Å“speaksÃ¢â‚¬Â about the tolerance in the plurality of religion and the principles of religious freedom in Islamic perspective.